Die politische Dimension der Anthropologie-Vorlesungen Kants - Salikov, Alexei (Studia z Historii Filozofii, 2020)
This article aims to establish a connection between Kant’s Lectures on Anthropology and his political writings. As the comparative analysis shows, the lectures contain a number of fragments that conceptually or even verbatim reproduce the ideas of Kant’s later published works on political topics. Given the fact that Kant did not give separate lectures on politics, Lectures on Anthropology represent the most important additional source of the Kantian political thought, allowing us to assume that they were a kind of sounding board which Kant used to think out loud and deliver the first versions of his socio-political ideas to his students, polishing them up before putting the finishing touches and publishing them for a larger audience. Lectures also help to trace the genesis of Kant’s individual political ideas, to discover changes in the perspective from which he viewed political events of his time and the historical process as a whole.